Insights on the emergence and conceptual evolution of coastal geography in France - Hermon, Elly (Riparia, 2016)
The paper provides an analytical overview of significant landmarks in the conceptual evolution of coastal geography in France since its emergence in the early 1950s. The paper comprises four sections dealing respectively with the following themes: 1. The conceptual trajectory of this field of study which resulted in significant broadening of its scope and methodology with the integration of physical geography and human geography dealing with coastal issues, which brought to adoption of a systemic approach and a broad vision characterizing global geography; 2. The remarkable complexity of the coastal space as reflected by the complex interactions between society and the natural environment and the resulting implications for the definition of this space; 3. The growing involvement of coastal geographers in management of the coastal space and the significance of their contribution to adopting an integrated management approach intended to advance sustainable development of coastal areas affected by rapidly increasing anthropization and natural forces with adverse impacts such as shoreline erosion and rising sea level; 4. The coastal vulnerability and environmental risk management, stressing the need for an appropriate land use planning.